2007
DOI: 10.1038/sj.npp.1301494
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Consequences of Chronic Alcohol Withdrawal: Expression Profiling Reveals Importance of Gender Over Withdrawal Severity

Abstract: While women are more vulnerable than men to many of the medical consequences of alcohol abuse, the role of sex in the response to ethanol is controversial. Neuroadaptive responses that result in the hyperexcitability associated with withdrawal from chronic ethanol likely reflect gene expression changes. We have examined both genders for the effects of withdrawal on brain gene expression using mice with divergent withdrawal severity that have been selectively bred from a genetically heterogeneous population. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(124 citation statements)
references
References 72 publications
13
111
0
Order By: Relevance
“…Female B6 mice had significantly greater intake of 6E, with a trend for an increase in 10E, when compared to their male counterparts. Nonetheless, these findings are consistent with clinical and preclinical studies documenting the existence of sex differences in sensitivity to a number of alcohol-related behaviors associated with neuroadaptation and reinforcement (e.g., Devaud et al, 2003;Finn et al, 2004aFinn et al, , 2004bGreen et al, 1999;Hashimoto and Wiren, 2007;Lancaster, 1995;Middaugh and Kelly, 1999;Rhodes et al, 2007;Vivian et al, 2001;Wiren et al 2006). …”
Section: Discussionsupporting
confidence: 82%
“…Female B6 mice had significantly greater intake of 6E, with a trend for an increase in 10E, when compared to their male counterparts. Nonetheless, these findings are consistent with clinical and preclinical studies documenting the existence of sex differences in sensitivity to a number of alcohol-related behaviors associated with neuroadaptation and reinforcement (e.g., Devaud et al, 2003;Finn et al, 2004aFinn et al, , 2004bGreen et al, 1999;Hashimoto and Wiren, 2007;Lancaster, 1995;Middaugh and Kelly, 1999;Rhodes et al, 2007;Vivian et al, 2001;Wiren et al 2006). …”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, increased vulnerability to EtOH-induced neurotoxicity in females remains controversial [reviewed in (51)] with additional studies needed to support or refute this hypothesis. This finding is buttressed by the observation that chronic ethanol exposure is associated with a strongly sexually dimorphic transcriptional response (44,118,119). In those studies, significantly regulated transcripts included several genes that are exclusively or predominantly expressed in astrocytes, suggesting that a component of the neuroadapative response in the brain after ethanol exposure reflects changes in astrocyte gene expression that are distinct between males and females.…”
Section: Introductionmentioning
confidence: 73%
“…Females have higher rates or greater severity of cardiomyopathy, peripheral neuropathy, some types of cancer and liver cirrhosis (5,59). Increased vulnerability to ethanol-induced brain damage in the prefrontal cortex in females has been observed in some studies (44,118). Other studies have not confirmed female vulnerability, but have noted different "brain morphological deficits" between males and females supporting the notion that neurodamage occurs via different mechanisms depending on sex (94).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the effect of sex was revealed in a recent study on gene expression in male and female rodent brains after 72 h exposure to ethanol vapours followed by 8 h withdrawal (49) .…”
Section: Sex-specific Action Of Alcoholmentioning
confidence: 99%